2017
DOI: 10.1007/s00246-017-1780-9
|View full text |Cite
|
Sign up to set email alerts
|

Acute Pulmonary Vasodilator Testing and Long-Term Clinical Course in Segmental Pulmonary Vascular Disease

Abstract: Results of acute pulmonary vasodilator testing (AVT) and the outcome of medical therapy have not been described in patients with segmental pulmonary vascular disease (SPVD). We sought to compare the pulmonary vasodilatory effects of oxygen, oxygen with nitric oxide, and diltiazem, and to describe the clinical course of patients with SPVD and pulmonary hypertension. A retrospective review of 16 patients with pulmonary hypertension and SPVD involving 2-3 major lung segments who underwent AVT between January 2000… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 18 publications
1
3
0
Order By: Relevance
“…Together with the observations that eNOS inhibition produced a larger increase in tPVRi in PVB as compared to sham, and the relatively modest vasodilation induced by SNP as compared to PDE5 inhibition, this suggests that the NO pathway is hyperactive in PVB pulmonary vasculature, probably as a compensatory mechanism, and that adding additional NO has a very limited effect. These data are consistent with the study of Domingo et al, which showed that NO on top of 100% oxygen did not induce further pulmonary vasodilation [25]. Interestingly, eNOS expression was higher in HP/HF as compared to HP/LF, and tended to be higher compared to the corresponding lung lobe of sham animals.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Together with the observations that eNOS inhibition produced a larger increase in tPVRi in PVB as compared to sham, and the relatively modest vasodilation induced by SNP as compared to PDE5 inhibition, this suggests that the NO pathway is hyperactive in PVB pulmonary vasculature, probably as a compensatory mechanism, and that adding additional NO has a very limited effect. These data are consistent with the study of Domingo et al, which showed that NO on top of 100% oxygen did not induce further pulmonary vasodilation [25]. Interestingly, eNOS expression was higher in HP/HF as compared to HP/LF, and tended to be higher compared to the corresponding lung lobe of sham animals.…”
Section: Discussionsupporting
confidence: 92%
“…Most patients with PVS [25], as well as swine with PVS [15], show a decrease in pulmonary artery pressure upon vasoreactivity testing with inhaled 100% oxygen. In our previous study, we showed that ET A/B blockade with tezosentan resulted in a decrease in tPVRi in swine with PVB, and that this vasodilator effect increased over time [17].…”
Section: Discussionmentioning
confidence: 99%
“…47 Although historically controversial, there is growing evidence suggesting not only the safety of pulmonary vasodilators in the setting of PVS but also efficacy and utility in patients with severe PVS. 47,50,65 Any use of standard pulmonary vasodilators in this population should be done so with due caution and carefully planned reevaluation to determine the efficacy or progression of PVS. Pulmonary vasodilators are never indicated with diffuse, symmetrical PVS, similar to the contraindication with the pulmonary veno-occlusive disease.…”
Section: Comorbiditiesmentioning
confidence: 99%
“…Catheterization allows for vasoreactivity testing in patients with PVS and pulmonary artery hypertension (PAH). Our center has been more aggressive about using pulmonary vasodilator therapy for patients with elevated PA pressures who have undergone such vasoreactivity assessment [17]. In recent years, patients with RV pressures > 50% systemic at catheterization are given a trial with pulmonary vasodilators while they are in the hospital.…”
Section: Diagnosis and Surveillancementioning
confidence: 99%